2011
DOI: 10.1186/1741-7015-9-77
|View full text |Cite
|
Sign up to set email alerts
|

Problematic internet usage in US college students: a pilot study

Abstract: BackgroundInternet addiction among US college students remains a concern, but robust estimates of its prevalence are lacking.MethodsWe conducted a pilot survey of 307 college students at two US universities. Participants completed the Internet Addiction Test (IAT) as well as the Patient Health Questionnaire. Both are validated measures of problematic Internet usage and depression, respectively. We assessed the association between problematic Internet usage and moderate to severe depression using a modified Poi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
89
10
14

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(131 citation statements)
references
References 34 publications
18
89
10
14
Order By: Relevance
“…Some studies have reported an association between Internet use and depression (e.g., Christakis, Moreno, Jelenchick, Myaing, & Zhou, 2011;Durkee, Kaess, Floderus, Carli, & Wasserman, 2011;Liu, Desai, Krishnan-Sarin, Cavallo, & Potenza, 2011). However, other studies have reported that aspects of Internet use such as Facebook use (i.e., social Internet use) is not linked to depression (Jelenchick, Eickhoff, & Moreno, 2013) despite warnings about so called "Facebook depression" (e.g., O'Keeffe & Clarke-Pearson, 2011).…”
Section: Compulsive Internet Usementioning
confidence: 99%
“…Some studies have reported an association between Internet use and depression (e.g., Christakis, Moreno, Jelenchick, Myaing, & Zhou, 2011;Durkee, Kaess, Floderus, Carli, & Wasserman, 2011;Liu, Desai, Krishnan-Sarin, Cavallo, & Potenza, 2011). However, other studies have reported that aspects of Internet use such as Facebook use (i.e., social Internet use) is not linked to depression (Jelenchick, Eickhoff, & Moreno, 2013) despite warnings about so called "Facebook depression" (e.g., O'Keeffe & Clarke-Pearson, 2011).…”
Section: Compulsive Internet Usementioning
confidence: 99%
“…Zhang et al (2008), Dixit et al (2010), Christakis et al (2011), andCasey (2012) all studied internet addiction in college students. In hypothesis 4 (H 4 ), the author suggests that college student mobile users have more severe mobile internet dependency than non-student users.…”
Section: Research Hypothesesmentioning
confidence: 99%
“…Family Control children's use of the Internet (4), intimate members of the family (3), pay attention to children's needs (8), managing children's plans (5), and engaging children in social activities (9).…”
Section: Social Supportmentioning
confidence: 99%
“…Education Life skills training (7), education about Internet usage (6), promote awareness about risks of internet addiction (7), leverage media, scientific workshops and research programs (6), and deliver education programs to primary school students about Internet usage (8).…”
Section: Appropriate Culturementioning
confidence: 99%
See 1 more Smart Citation